Engineering mechanics [2nd ed.] - Harbola, Manoj K. (New Delhi Cengage Learning, 2012)
Engineering Mechanics (2e) is designed to serve as a textbook for a single-semester undergraduate course on engineering mechanics. It provides a lucid introduction to both statics and dynamics. Beginning with a review of vector algebra and Newton's laws, the book goes on to cover concepts of statics, such as equilibrium of bodies, plane trusses, friction and the method of virtual work, employing both the scalar and the vector approach. This is followed by an extensive discussion of topics in dynamics, including momentum, work and energy, rotational dynamics and harmonic oscillators. A chapter on non-inertial frames completes the utility of this book as a first-level text on engineering mechanics. Written in an easy-to-understand manner, the book includes a large number of solved examples which illustrate problem-solving methodology. A summary at the end of each chapter reviews the key concepts discussed in the chapter. An extensive set of end-of-chapter exercises, which include both long problems and objective-type questions, are supplemented by conceptual checkpoints interspersed throughout the text.
Keywords: Mechanics; Applied statics; Dynamics